IMPLEMENTASI RASI BINTANG NAVIGASI BUGIS PERSPEKTIF ILMU FALAK - Sadri s Saputra; Muammar Bakri (HISABUNA: Jurnal Ilmu Falak, 2020)
This study discusses the implementation of Bugis navigation constellations in Falak Science. Star is a form of the sign of the greatness of God Almighty, which was created in vain, it has an important role in human life, one of which is that stars can be used as directions, as is known by the Bugis people in South Sulawesi, which makes stars as system navigation in the voyage which came to be called Bugis navigation. The aim of this research is to find out the implementation of the Bugis navigation constellations in Falak Science. This research belongs to library research, using a multidisciplinary approach, namely: the syar'i approach, the philosophical approach and the astronomical approach, where the data deemed relevant in the object of this study are analyzed and studied in depth by the author then poured in the form of discussion in answering the problem.